Strippable flame retardant coating for magnesium alloy and preparation method thereof
By preparing peelable flame retardant coatings for magnesium alloys, the problems of magnesium alloy substrates are solved, and the excellent flame retardant properties and peelability of the coating are achieved.
Patent Information
- Application Number
- CN202411602968.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Magnesium alloys are prone to corrosion and scratches during processing, assembly and transportation. The existing coatings are inadequate flame retardant and are prone to corrosive magnesium alloy substrates.
Using a method of preparing a peelable flame retardant coating for magnesium alloy, a coating with excellent mechanical properties and peelable properties is prepared by mixing acrylic emulsion, polytetrafluoroethylene emulsion, emulsified wax and anti-rust agent, multiple flame retardant addition and pH adjustment processes are performed, and thickener and defoaming agent are added to prepare a coating with excellent mechanical properties and peelable properties.
It effectively improves the flame retardant performance of the paint and the protective effect of the magnesium alloy substrate, avoids the paint from corroding the magnesium alloy substrate, and improves the spraying performance and sag resistance of the paint.
Smart Images

Figure CN119144198B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of alloy coatings, and in particular to a strippable flame-retardant coating for magnesium alloys and a preparation method of the strippable flame-retardant coating for magnesium alloys. Background Art
[0002] Magnesium alloys have the advantages of light weight, high strength and high stability in extreme environments, and have been widely used in aerospace, new energy vehicles, shipbuilding and other fields. However, they are easily corroded and scratched during processing, assembly and transportation, affecting their performance and appearance.
[0003] Spraying coating on the surface of magnesium alloy is an effective way to protect magnesium alloy. At present, the coating has the problems of insufficient flame retardancy and easy corrosion of magnesium alloy substrate.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The purpose of the present disclosure is to provide a strippable flame-retardant coating for magnesium alloys and a method for preparing the strippable flame-retardant coating for magnesium alloys, thereby overcoming the problems of insufficient flame retardancy and easy corrosion of the magnesium alloy substrate of the coating at least to a certain extent.
[0006] According to a first aspect of the present disclosure, a method for preparing a strippable flame-retardant coating for magnesium alloy is provided, comprising: mixing an acrylic emulsion, a polytetrafluoroethylene emulsion, an emulsified wax and a rust inhibitor to obtain a first emulsion; performing a flame retardant adding process for a predetermined number of times on the first emulsion to obtain a second emulsion; adding a thickener and a defoaming agent to the second emulsion to obtain a strippable flame-retardant coating for magnesium alloy; wherein the flame retardant adding process for a predetermined number of times on the first emulsion to obtain the second emulsion comprises: adding a bromine antimony flame retardant to the first emulsion to obtain a first intermediate emulsion; adjusting the pH of the first intermediate emulsion to be consistent with the pH of the first emulsion using a pH adjuster to obtain a second intermediate emulsion; if the number of times the bromine antimony flame retardant is added does not reach the predetermined number of times, adding the bromine antimony flame retardant to the second intermediate emulsion to obtain the first intermediate emulsion; if the number of times the bromine antimony flame retardant is added reaches the predetermined number of times, using the second intermediate emulsion as the second emulsion.
[0007] Optionally, acrylic emulsion, polytetrafluoroethylene emulsion, emulsified wax and rust inhibitor are mixed to obtain a first emulsion, including: in a water bath environment, acrylic emulsion, polytetrafluoroethylene emulsion and emulsified wax are mixed to obtain a first initial emulsion; pH of the first initial emulsion is adjusted to 8.0 to 8.2 by a pH adjuster to obtain a second initial emulsion; and rust inhibitor is added to the second initial emulsion to obtain the first emulsion.
[0008] Optionally, the water bath temperature of the water bath environment is 10°C to 15°C.
[0009] Optionally, the solid content of the acrylic emulsion is 45% to 50%, the viscosity is 1000cps to 1200cps, and the pH value is 5 to 7; the solid content of the polytetrafluoroethylene emulsion is 55% to 65%; the solid content of the emulsified wax is 25% to 40%; wherein the mass ratio of the acrylic emulsion, the polytetrafluoroethylene emulsion, and the emulsified wax is (5-10):(1-2):(3-5).
[0010] Optionally, the rust inhibitor is an organic complex, has a pH value of 9 to 11, and a mass content of 0.5% to 1% of the first emulsion.
[0011] Optionally, the total added mass of the bromine antimony flame retardant is 4% to 10% of the first emulsion; wherein, during the predetermined number of flame retardant additions, the bromine antimony flame retardant is added at intervals of 3 to 7 minutes after each pH adjustment.
[0012] Optionally, the thickener is a composite thickener, and the preparation method further includes: adding attapulgite to deionized water under stirring conditions of 1800 r / min to 2500 r / min to obtain an intermediate thickener; wherein, in terms of mass, the attapulgite is 5 to 15 parts and the deionized water is 85 to 95 parts; keeping the stirring conditions unchanged, adding 10 to 15 parts of an acrylic copolymer aqueous thickener to the intermediate thickener to obtain a composite thickener.
[0013] Optionally, the mass of the composite thickener is 4% to 7% of the first emulsion.
[0014] Optionally, the defoaming agent is a polyether siloxane copolymer aqueous defoaming agent, and its mass accounts for 0.3% to 1.5% of the first emulsion.
[0015] According to a second aspect of the present disclosure, a strippable flame-retardant coating for magnesium alloy is provided. The strippable flame-retardant coating for magnesium alloy is prepared by any of the above-mentioned methods for preparing the strippable flame-retardant coating for magnesium alloy.
[0016] In the scheme of the exemplary embodiment of the present disclosure, on the one hand, by performing the process of flame retardant addition and pH adjustment multiple times, the consumption of the rust inhibitor can be avoided, thereby preventing the coating from corroding the magnesium alloy substrate, and at the same time, the flame retardant properties of the coating can be improved; on the other hand, by adjusting the acid-base environment, the decomposition of the bromine antimony flame retardant to produce halides that corrode the substrate can be avoided; on the other hand, through the thickener adjustment method of the present scheme, the spraying performance and anti-sagging performance of the coating can be improved; on the other hand, the emulsion configuration of the scheme of the present disclosure enables the coating to have excellent mechanical properties and strippability after curing.
[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0019] Figure 1 A flow chart schematically shows a method for preparing a strippable flame-retardant coating for magnesium alloy according to an exemplary embodiment of the present disclosure.
[0020] Figure 2 A flow chart schematically shows a process for generating a second emulsion from a first emulsion.
[0021] Figure 3 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 1 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0022] Figure 4 A schematic diagram showing the peelability of a coating prepared using the coating of Example 1 is shown.
[0023] Figure 5 A schematic diagram of the flame retardant performance test of the coating of Example 1 is shown; A is a schematic diagram of spraying fire to the coating at 1 second, B is a diagram of the flame retardant effect of the coating at 3 seconds, C is a schematic diagram of spraying fire to the coating at 5 seconds, and D is a diagram of the flame retardant effect of the coating at 7 seconds.
[0024] Figure 6 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 2 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0025] Figure 7 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 3 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0026] Figure 8 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 4 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0027] Fig. 9 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Comparative Example 1 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0028] Fig.10 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Comparative Example 2 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping. DETAILED DESCRIPTION
[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0030] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual conditions. In addition, all the terms "first", "second", etc. below are only for the purpose of distinction and should not be used as limitations of the present disclosure.
[0031] At present, most strippable coatings are water-based coatings, which are easy to corrode the active magnesium alloy substrate. Introducing rust inhibitors into coatings is an effective means to solve corrosion. However, rust inhibitors are usually strongly alkaline and are easily neutralized by acidic substances in coatings with complex ingredients and become ineffective. In addition, most strippable coatings are flammable and combustion-supporting under open flames, which will bring safety hazards to the flammable magnesium alloy substrate. In addition, introducing bromine antimony flame retardants is an effective way to improve the flame retardancy of coatings. However, since bromine antimony flame retardants are relatively sensitive to acidity and alkalinity, they are very easy to decompose and produce halides, which in turn aggravates the corrosion of magnesium alloy substrates.
[0032] In order to solve or at least alleviate the problem of insufficient flame retardancy of the coating and easy corrosion of the magnesium alloy substrate, the embodiment of the present disclosure provides a new preparation scheme of a strippable flame retardant coating for magnesium alloys, which is a passivation type water-based strippable flame retardant coating.
[0033] Figure 1 The flowchart of the method for preparing the strippable flame-retardant coating for magnesium alloy according to the exemplary embodiment of the present disclosure is schematically shown. Figure 1 The method for preparing the strippable flame-retardant coating for magnesium alloy according to the embodiment of the present disclosure comprises the following steps:
[0034] S12. The acrylic emulsion, the polytetrafluoroethylene emulsion, the emulsified wax and the rust inhibitor are mixed to obtain a first emulsion.
[0035] In an exemplary embodiment of the present disclosure, the acrylic emulsion has a solid content of 45% to 50%, a viscosity of 1000 cps to 1200 cps, and a pH of 5 to 7. The solid content of the polytetrafluoroethylene (PTFE) emulsion is 55% to 65%. The solid content of the emulsified wax is 25% to 40%. The mass ratio of the acrylic emulsion, the polytetrafluoroethylene emulsion, and the emulsified wax is (5-10): (1-2): (3-5). The rust inhibitor is an organic complex, the pH is 9 to 11, and the mass of the rust inhibitor is 0.5% to 1% of the first emulsion.
[0036] First, in a water bath environment, acrylic emulsion, polytetrafluoroethylene emulsion and emulsified wax are mixed to obtain a first initial emulsion, wherein the water bath temperature of the water bath environment is controlled to be 10° C. to 15° C., which can be achieved by a water bath pot containing ice or a water bath pot having a temperature control function.
[0037] Specifically, a beaker is placed in a water bath, acrylic emulsion, polytetrafluoroethylene emulsion and emulsified wax are added to the beaker, and stirred at 1000 r / min to 1200 r / min for 10 min to 15 min to obtain a first initial emulsion. It is understood that the stirring process described in the present disclosure is achieved with the aid of a stirrer, and the speed is the speed required when the stirrer implements the exemplary solution of the present disclosure.
[0038] Next, the pH of the first initial emulsion was adjusted to 8.0 to 8.2 using a pH adjuster to obtain a second initial emulsion.
[0039] Specifically, after obtaining the first initial emulsion, the rotation speed is increased to 1800 r / min to 2000 r / min, and the first initial emulsion is titrated to a pH of 8.0 to 8.2 using a pH adjuster. The present disclosure does not limit the type of pH adjuster, for example, ammonia water, sodium hydroxide solution, etc. are all easily understood optional adjusters.
[0040] Then, a rust inhibitor is added to the second initial emulsion to obtain a first emulsion.
[0041] Specifically, while maintaining the rotation speed unchanged, the rust inhibitor can be added to the second initial emulsion, and the first emulsion can be obtained after stirring for 10 to 15 minutes.
[0042] S14. Performing a flame retardant adding process for a predetermined number of times on the first emulsion to obtain a second emulsion.
[0043] It can be understood that the predetermined number of times is related to the amount of flame retardant added and the quality of the first emulsion, for example, 8 to 15 times, which is not limited in the present disclosure.
[0044] In an exemplary embodiment of the present disclosure, the added flame retardant is a bromine antimony flame retardant, and the total added mass of the bromine antimony flame retardant may be 4% to 10% of the mass of the first emulsion.
[0045] Reference below Figure 2 The process of generating the second emulsion from the first emulsion is described.
[0046] In step S202, a bromine antimony flame retardant is added to the first emulsion to obtain a first intermediate emulsion.
[0047] Specifically, at 1800 r / min to 2000 r / min, the bromine antimony flame retardant is added into the first emulsion to obtain the first intermediate emulsion.
[0048] In step S204, a pH adjusting agent is used to adjust the pH of the first intermediate emulsion to be consistent with the pH of the first emulsion to obtain a second intermediate emulsion. The present disclosure does not limit the type of the pH adjusting agent.
[0049] In step S206, it is determined whether the number of times of adding the bromine antimony flame retardant reaches a predetermined number. If not, step S208 is executed; if so, step S210 is executed.
[0050] In step S208, a bromine antimony flame retardant may be added to the second intermediate emulsion to obtain a first intermediate emulsion. In this case, the implementation steps jump back to step S204.
[0051] It should be noted that, in order to achieve a sufficient reaction, the bromine antimony flame retardant may be added after an interval of 3 to 7 minutes after each pH adjustment.
[0052] In step S210, the second intermediate emulsion is used as the second emulsion.
[0053] For example, the total amount of bromine antimony flame retardant added is 10% of the mass of the first emulsion, and the adding method is to divide the bromine antimony flame retardant into 10 equal parts, that is, the above-mentioned predetermined number of times is 10, and each time the bromine antimony flame retardant is added and the pH is adjusted, the bromine antimony flame retardant is added again after an interval of 5 minutes.
[0054] S16. Adding a thickener and a defoamer to the second emulsion to obtain a strippable flame-retardant coating for magnesium alloy.
[0055] In an exemplary embodiment of the present disclosure, the defoaming agent is a polyether siloxane copolymer-based aqueous defoaming agent, and the mass of the defoaming agent is 0.3% to 1.5% of the first emulsion.
[0056] In addition, in order to enhance the sprayability and anti-sagging properties of the coating, the present embodiment improves the thickener, which is a composite thickener. The preparation process of the composite thickener using the present solution is described below.
[0057] First, under the stirring condition of 1800 r / min to 2500 r / min, attapulgite is added to deionized water to obtain an intermediate thickener; wherein, by weight, the attapulgite is 5 to 15 parts, and the deionized water is 85 to 95 parts.
[0058] Next, while maintaining the stirring condition unchanged, 10 to 15 parts of an acrylic copolymer aqueous thickener are added to the intermediate thickener to obtain a composite thickener. Specifically, the mass of the composite thickener is 4% to 7% of the first emulsion.
[0059] For example, 10 parts of attapulgite are slowly added to 90 parts of deionized water under stirring at 2000 r / min. After stirring for 30 minutes, 10 parts of acrylic copolymer aqueous thickener are added dropwise while maintaining the stirring speed unchanged. After continuing stirring for 10 minutes, a composite thickener is obtained.
[0060] After the second emulsion is obtained in step S14, the rotation speed can be reduced to 1200 r / min to 1500 r / min. The thickener is added to the second emulsion and stirred for 10 min to 15 min. Then, the rotation speed is reduced to 900 r / min to 1000 r / min, a defoaming agent is added, and stirred for another 5 min to 10 min, thereby obtaining the strippable flame-retardant coating for magnesium alloys described in the present disclosure.
[0061] Through the preparation scheme of the strippable flame-retardant coating for magnesium alloy of the embodiment of the present disclosure, on the one hand, by compounding the emulsion, the coating has excellent mechanical properties and strippability relative to the substrate after curing; on the other hand, by adding bromine antimony flame retardant in small amounts and multiple times, the rust inhibitor can be avoided from being consumed, and the water-based coating can be prevented from corroding the magnesium alloy substrate, while also improving the flame retardant safety of the coating; on the other hand, through the modification of the thickener, the spraying performance and anti-sagging performance of the coating are greatly improved. According to experiments, the coating can be sprayed continuously to 1500μm without sagging and the surface is smooth.
[0062] The exemplary embodiments of the present disclosure are described below through examples and comparative examples.
[0063] Example 1
[0064] First, place a beaker in an ice-water bath at 15°C, and place 25 g of acrylic emulsion, 5 g of PTFE emulsion, and 20 g of emulsified wax in the beaker in turn, stirring at 1000 r / min for 10 min. Increase the speed to 2000 r / min, add a pH adjuster until the pH value reaches 8.0, then add 0.26 g of rust inhibitor, stir for 10 min, and the resulting mixture is marked as the first emulsion. Among them, the solid content of the acrylic emulsion is 50%, the viscosity is 1200 cps, and the pH is 5; the solid content of the polytetrafluoroethylene emulsion is 55%, and the solid content of the emulsified wax is 25%.
[0065] Next, under the stirring condition of 2000r / min, 2.2g of bromine antimony flame retardant was divided into 10 equal parts, and one part was added every 5 minutes. Before adding the next part of bromine antimony flame retardant, pH adjusting agent was used for titration until the pH was consistent with that of the first emulsion. After all the bromine antimony flame retardant was added, stirring was continued for 30 minutes to obtain the second emulsion.
[0066] Then, the speed was reduced to 1500 r / min, 2.2 g of the modified composite thickener was added, and the mixture was stirred for 10 min. Then, the speed was reduced to 1000 r / min, 0.16 g of a polyether siloxane copolymer aqueous defoaming agent was added, and the mixture was stirred for 5 min to obtain the passivation type water-based strippable flame-retardant coating for magnesium alloy corresponding to Example 1.
[0067] Figure 3A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 1 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0068] refer to Figure 3 The coating surface of the coating of Example 1 is smooth and flat, and the magnesium alloy substrate after peeling off the coating is flat, without pits and corrosion spots.
[0069] Figure 4 Schematic diagram showing the peelability of the coating prepared by using the coating of Example 1. Figure 4 In the peeling schematic diagram, it can also be seen that the excellent peelability brought about by the application of Example 1 of the present disclosure.
[0070] Figure 5 A schematic diagram of the flame retardant performance test of the coating of Example 1 is shown; A is a schematic diagram of spraying fire to the coating at 1 second, B is a diagram of the flame retardant effect of the coating at 3 seconds, C is a schematic diagram of spraying fire to the coating at 5 seconds, and D is a diagram of the flame retardant effect of the coating at 7 seconds.
[0071] refer to Figure 5 Through the two groups of experiments of 1s and 3s and 5s and 7s, it can be seen that the coating prepared by the scheme of Example 1 of the present disclosure has self-extinguishing properties after leaving the fire source, indicating that the coating of Example 1 of the present disclosure has good flame retardancy.
[0072] Example 2
[0073] First, place a beaker in an ice-water bath at 15°C, and sequentially place 35 g of acrylic emulsion, 5 g of PTFE emulsion, and 20 g of emulsified wax in the beaker, stirring at 1000 r / min for 10 min. Increase the speed to 2000 r / min, add a pH adjuster until the pH value reaches 8.1, then add 0.42 g of a rust inhibitor, stir for 10 min, and the resulting mixture is marked as the first emulsion. Among them, the solid content of the acrylic emulsion is 48%, the viscosity is 1150 cps, and the pH is 6; the solid content of the polytetrafluoroethylene emulsion is 60%, and the solid content of the emulsified wax is 30%.
[0074] Next, under the stirring condition of 2000r / min, 3.6g of bromine antimony flame retardant was divided into 10 equal parts, and one part was added every 3 minutes. Before adding the next part of bromine antimony flame retardant, pH adjuster was used for titration until the pH was consistent with that of the first emulsion. After all the bromine antimony flame retardant was added, stirring was continued for 30 minutes to obtain the second emulsion.
[0075] Then, the speed was reduced to 1500 r / min, 3 g of the modified composite thickener was added, and stirred for 10 min. Then, the speed was reduced to 1000 r / min, 0.42 g of a polyether siloxane copolymer aqueous defoaming agent was added, and stirred for 5 min to obtain the passivation type water-based strippable flame-retardant coating for magnesium alloy corresponding to Example 2.
[0076] Figure 6 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 2 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0077] refer to Figure 6 The coating surface of the coating of Example 2 is smooth and flat, and the magnesium alloy substrate after peeling off the coating is flat, without pits and corrosion spots.
[0078] Example 3
[0079] First, place a beaker in an ice-water bath at 10°C, and place 45 g of acrylic emulsion, 5 g of PTFE emulsion, and 20 g of emulsified wax in the beaker in turn, stirring at 1000 r / min for 10 min. Increase the speed to 2000 r / min, add a pH adjuster until the pH value reaches 8.1, then add 0.63 g of rust inhibitor, stir for 10 min, and the resulting mixture is marked as the first emulsion. Among them, the solid content of the acrylic emulsion is 45%, the viscosity is 1000 cps, and the pH is 7; the solid content of the polytetrafluoroethylene emulsion is 65%, and the solid content of the emulsified wax is 40%.
[0080] Next, under the stirring condition of 2000r / min, 5.6g of bromine antimony flame retardant was divided into 10 equal parts, and one part was added every 7 minutes. Before adding the next part of bromine antimony flame retardant, pH adjusting agent was used for titration until the pH was consistent with that of the first emulsion. After all the bromine antimony flame retardant was added, stirring was continued for 30 minutes to obtain the second emulsion.
[0081] Then, the speed was reduced to 1500 r / min, 4.2 g of the modified composite thickener was added and stirred for 10 min, and then the speed was reduced to 1000 r / min, 0.77 g of a polyether siloxane copolymer aqueous defoaming agent was added, and stirred for 5 min to obtain the passivation type water-based strippable flame-retardant coating for magnesium alloy corresponding to Example 3.
[0082] Figure 7 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 3 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0083] refer to Figure 7The coating surface of the coating of Example 3 is smooth and flat, and the magnesium alloy substrate after peeling off the coating is flat, without pits and corrosion spots.
[0084] Example 4
[0085] First, place a beaker in an ice-water bath at 12°C, and place 50g of acrylic emulsion, 5g of PTFE emulsion, and 20g of emulsified wax in the beaker in turn, stirring at 1000r / min for 10min. Increase the speed to 2000r / min, add a pH adjuster until the pH value reaches 8.2, then add 0.75g of a rust inhibitor, stir for 10min, and the resulting mixture is marked as the first emulsion. Among them, the solid content of the acrylic emulsion is 45%, the viscosity is 1000cps, and the pH is 7; the solid content of the polytetrafluoroethylene emulsion is 55%, and the solid content of the emulsified wax is 40%.
[0086] Next, under the stirring condition of 2000r / min, 7.5g of bromine antimony flame retardant was divided into 10 equal parts, and one part was added every 5 minutes. Before adding the next part of bromine antimony flame retardant, pH adjusting agent was used for titration until the pH was consistent with that of the first emulsion. After all the bromine antimony flame retardant was added, stirring was continued for 30 minutes to obtain the second emulsion.
[0087] Then, the speed was reduced to 1500 r / min, 5.25 g of the modified composite thickener was added and stirred for 10 min, and then the speed was reduced to 1000 r / min, 1.12 g of a polyether siloxane copolymer aqueous defoaming agent was added, and stirred for 5 min to obtain the passivation type water-based strippable flame-retardant coating for magnesium alloy corresponding to Example 4.
[0088] Figure 8 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Example 4 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0089] refer to Figure 8 The coating surface of the coating of Example 4 is smooth and flat, and the magnesium alloy substrate after peeling off the coating is flat, without pits and corrosion spots.
[0090] Comparative Example 1
[0091] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not include a pH adjustment process.
[0092] Comparative Example 2
[0093] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the flame retardant is added to the emulsion at one time.
[0094] Fig. 9A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Comparative Example 1 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping. Fig.10 A schematic diagram comparing the appearance of the coating before stripping and the magnesium alloy substrate after stripping of the coating of Comparative Example 2 is shown; wherein A is a schematic diagram of the appearance of the coating before stripping, and B is a schematic diagram of the appearance of the magnesium alloy substrate after stripping.
[0095] refer to Fig. 9 and Fig.10 , the coating produced bubbles, and after the coating was stripped, visible corrosion spots appeared on the magnesium alloy substrate. From Comparative Examples 1 and 2, it can be seen that the solution of the embodiment of the present disclosure can solve the corrosion problem of the strippable coating on the magnesium alloy substrate.
[0096] Furthermore, the present disclosure also provides a strippable flame-retardant coating for magnesium alloys, and the strippable flame-retardant coating for magnesium alloys is prepared using the above-mentioned preparation method.
[0097] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0098] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0099] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.
[0100] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing a strippable flame-retardant coating for magnesium alloy, characterized in that: include: Mixing acrylic emulsion, polytetrafluoroethylene emulsion, emulsified wax and rust inhibitor to obtain a first emulsion; Adding the bromine antimony flame retardant to the first emulsion in N times to obtain a second emulsion; adding a thickener and a defoamer to the second emulsion to obtain a strippable flame-retardant coating for magnesium alloy; The step of adding the bromine antimony flame retardant to the first emulsion N times to obtain the second emulsion comprises: S1. Divide the bromine antimony flame retardant into N parts; S2. adding a portion of the bromine antimony flame retardant to the first emulsion; S3. adjusting the pH using a pH adjusting agent until the pH is consistent with that of the first emulsion; S4. Repeat steps S2-S3 until all the bromine antimony flame retardant is added to obtain a second emulsion; The value of N is 8-15, and N is an integer.
2. The preparation method according to claim 1, characterized in that: The acrylic emulsion, the polytetrafluoroethylene emulsion, the emulsified wax and the rust inhibitor are mixed to obtain a first emulsion, comprising: In a water bath environment, acrylic emulsion, polytetrafluoroethylene emulsion and emulsified wax are mixed to obtain a first initial emulsion; Using a pH adjuster to adjust the pH of the first initial emulsion to 8.0 to 8.2 to obtain a second initial emulsion; A rust inhibitor is added to the second initial emulsion to obtain a first emulsion.
3. The preparation method according to claim 2, characterized in that: The water bath temperature of the water bath environment is 10°C to 15°C.
4. The preparation method according to claim 1, characterized in that: The acrylic emulsion has a solid content of 45% to 50%, a viscosity of 1000 cps to 1200 cps, and a pH value of 5 to 7; The solid content of the polytetrafluoroethylene emulsion is 55% to 65%; The solid content of the emulsified wax is 25% to 40%; Wherein, the mass ratio of the acrylic emulsion, the polytetrafluoroethylene emulsion and the emulsified wax is (5-10): (1-2): (3-5).
5. The preparation method according to claim 1, characterized in that: The rust inhibitor is an organic complex, has a pH value of 9 to 11, and accounts for 0.5% to 1% of the first emulsion in terms of mass.
6. The preparation method according to claim 1, characterized in that: The total added mass of the bromine antimony flame retardant is 4% to 10% of the first emulsion; Wherein, after each pH adjustment, the bromine antimony flame retardant is added at intervals of 3 to 7 minutes.
7. The preparation method according to any one of claims 1 to 6, characterized in that The thickener is a composite thickener, and the preparation method of the composite thickener comprises: Under stirring conditions of 1800 r / min to 2500 r / min, attapulgite is added to deionized water to obtain an intermediate thickener; wherein, by weight, the attapulgite is 5 to 15 parts, and the deionized water is 85 to 95 parts; Keeping the stirring conditions unchanged, 10 to 15 parts of an acrylic copolymer aqueous thickener are added to the intermediate thickener to obtain the composite thickener.
8. The preparation method according to claim 7, characterized in that: The mass of the composite thickener is 4% to 7% of the first emulsion.
9. The preparation method according to claim 1, characterized in that: The defoamer is a polyether siloxane copolymer water-based defoamer, and its mass accounts for 0.3% to 1.5% of the first emulsion.
10. A strippable flame retardant coating for magnesium alloy, characterized in that: The strippable flame-retardant coating for magnesium alloy is prepared by the method for preparing the strippable flame-retardant coating for magnesium alloy according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-flame-retardant waterborne acrylic resin emulsion and high-flame-retardant coating
CN108624182A
Ultrathin fireproof coating material and preparation method thereof
CN111592825A